Telerehabilitation and onsite rehabilitation effectively improve quality of life, fatigue, balance, and cognition in people with multiple sclerosis: an interventional study - Petracca, Maria; Petsas, Nikolaos; Sellitto, Giovanni; Ruotolo, Ilaria; Livi, Chiara; Bonanno, Valeria; Felicetti, Federica; Ianniello, Antonio; Ruggieri, Serena; Borriello, Giovanna; Pozzilli, Carlo (Frontiers in Neurology, 2024)
Background Telerehabilitation (TR) offers a valuable opportunity to improve access to care, and has shown results comparable to on-site rehabilitation (SR) across different conditions. Aim of the present study was to explore the efficacy of TR and SR in improving clinically meaningful outcomes in people with multiple sclerosis (pwMS).Enrolled subjects were assigned to two treatment arms (6-week TR intervention vs. 6-week SR intervention). Pre-and post-intervention evaluation included assessment of global well-being (Multiple Sclerosis Quality of Life-54 scale -QoL), fatigue (Fatigue Severity Status scale-FSS), cognitive (Symbol Digit Modalities Test-SDMT) and balance dysfunction (Berg Balance Scale-BBS). Group level and single-subject improvements were considered as outcome measures, with QoL as primary endpoint. A paired t-test was applied for overall QoL score, physical and mental composites, to determine significant group changes over time for the whole pwMS group. An independent sample t-test was applied to assess differences in baseline and follow-up performance, as well as changes over time between intervention groups (TR and SR). The same analysis was repeated for the other clinical domains (FSS, BBS, SDMT). Minimal clinically important difference (MCID) according to treatment group (TR vs SR) was explored via logistic regression. A multiple linear regression model was applied to evaluate the impact of baseline clinical-demographic features on the observed post-intervention modifications.Results Fifty-one subjects completed the study (37 females, mean age 46.3 ±9.8, median Expanded Disability Status Scale 3.5, min. 2 max. 6.5). The entire sample showed benefit from the rehabilitation treatment, either focusing on group or individual level outcomes, with significant improvements observed in all domains for both intervention groups (TR vs SR) (quality of life p=0.005; fatigue and balance p<0.001; cognition p=0.003).3 Conclusions SR and TR approaches were effective in improving the perception of fatigue, cognitive performance, balance and quality of life in a population of MS patients with moderate disability.